A Geospatial approach to determine Lake Depth and Configuration of Reingkhyongkine (Pukur Para) Lake, Rangamati Hill District, Bangladesh with Multi-Temporal Satellite data - Nath, Biswajit; Acharjee, Shukla; Mitra, Atin Kumar; Majumder, Debabrata; Murgante, Beniamino (Journal of Environmental Accounting and Management, 2026)
Reingkhyongkine (Pukur Para) Lake is the largest hilly natural lake under Belaichhari Upazila in the Hill district of Rangamati, Bangladesh. Due to remoteness and rugged terrain this lake is never being investigated and not documented in the literature. This research is done following standard method and state-of-art-technology. As natural resource management foster sustainable development the present research is of immense importance. Global Positioning System (GPS) is used for water depth point positioning along with sounding techniques was used for water depth measurement. The highest and lowest depths are observed 145 m and 0.50 m respectively. The worldwide available Landsat 8 OLI/TIRS imagery of 13 May 2015 was considered as the base imagery to know the lake area at present context compare with other different years. The Lake depth and 3D configuration maps are developed based on field depth and derived contour data. In addition to this, surface elevation profile in different direction of lake and bathymetric mapping based on longitudinal and horizontal transect bottom topographic profile, lake surface area and water volume are also calculated to understand the real scenario of this largest lake. All these studies are integrated with local as well as the regional geological structures. The study using geo-integrated technology on Reingkhyongkine lake reveals that the changes of lake area which is 35.02 hectare (May 2015 Landsat 8 OLI Imagery), 40.65 hectare and 34.91 hectare (2010 and 1989 Landsat TM imagery) respectively which indicate an decreasing-increasing-decreasing trend scenario and changing at the rate of 0.11 percent per year and this changing phenomenon is related with the active tectonism of the area as the study area has suffered extensive thrusting, faulting and folding. Besides this the surface elevation of lake is not similar and it varies from 353 meter to 409 meters. Results shows that changes in the configuration and reduction of water volume of Reingkhyongkine Lake establish fragile conditions which indicate of its future drying status and needs continuous monitoring of water depth by considering environmental factors which are involved for the lake changes and finally researcher seeks urgent attention to international scientific community for protection and conservation of this hilly natural lake.